A bacterial glycoengineered antigen for improved serodiagnosis of porcine brucellosis - Cortina, María Eugenia (2016)
Brucellosis is a highly zoonotic disease that affects animals and human beings. Brucella suis is the etiological agent of porcine brucellosis and one of the major human brucellosis pathogens. Laboratory diagnosis of porcine brucellosis mainly relies on serological tests, and it has been widely demonstrated that serological assays based on the detection of anti O-polysaccharide antibodies are the most sensitive tests. Here, we validate a recombinant glycoprotein antigen, an N-formylperosamine O-polysaccharide protein conjugate (OAg-AcrA), for diagnosis of porcine brucellosis. An indirect immunoassay based on the detection of anti-O-polysaccharide IgG antibodies was developed coupling OAg-AcrA to enzyme-linked immunosorbent assay plates (glycoiELISA). To validate the assay, 563 serum samples obtained from experimentally infected and immunized pigs, as well as animals naturally infected with B. suis biovar 1 or 2, were tested. A receiver operating characteristic (ROC) analysis was performed, and based on this analysis, the optimum cutoff value was 0.56 (relative reactivity), which resulted in a diagnostic sensitivity and specificity of 100% and 99.7%, respectively. A cutoff value of 0.78 resulted in a test sensitivity of 98.4% and a test specificity of 100%. Overall, our results demonstrate that the glyco-iELISA is highly accurate for diagnosis of porcine brucellosis, improving the diagnostic performance of current serological tests. The recombinant glycoprotein OAg-AcrA can be produced in large homogeneous batches in a standardized way, making it an ideal candidate for further validation as a universal antigen for diagnosis of "smooth" brucellosis in animals and humans.